Nitrogen fertilizer application for improving the biomass, quality, and nitrogen fixation of alfalfa (Medicago sativa L.) at different growth stages in a saline‒alkali soil - Weifan Wan; Qian Liu; Ke Li; Kun Zhao; Fei Qi; Yuanshuo Li; Zhi Sun; Haigang Li (PeerJ)
Background The application of nitrogen (N) fertilizer to alfalfa (Medicago sativa L.) has received little attention due to the ability of this plant to fix N. However, N deficiency stress is often observed in marginal lands of China, especially in saline–alkali soils. Thus, this study aimed to assess the response of alfalfa yield, quality, N fixation, and soil N concentration to N fertilizer application at different stages in saline–alkali soil of Inner Mongolia. A 2-year (2020 and 2021) field experiment with five N fertilizer application rates, namely, 0 (N0), 20 (N20), 60 (N60), 120 (N120) and 180 (N180) kg N ha−1, was conducted in Inner Mongolia. Results The results showed that N fertilizer application of 180 kg ha−1 significantly increased the total alfalfa yield by 29%–32% by improving the stem‒leaf ratio; however, it didn’t lead to a further increase in alfalfa quality. N fertilizer applications of 60 and 120 kg ha−1 significantly improved the crude protein by 10.6%–22.7% and reduced the acid or neutral detergent fiber by 10.0%–18.7% in vegetative and bud stages, respectively, by improving the leaf N concentration. Furthermore, the fraction of N derived from the atmosphere reached 68.6%, with a significant increase in the corresponding amount of N fixed in N60. Soil NO3−-N concentrations significantly increased by 24.1%–33.3%, and NH4+-N concentrations increased by 1 to 3 times when N fertilizer application exceeded 120 kg N ha−1 compared with that in N0. Conclusions Overall, this study revealed the essential role of N fertilizer application at low rates in alfalfa production, as this practice not only increases alfalfa yield but also improves N fixation in saline‒alkali soil. However, it did not result in further improvement in alfalfa quality at the early flowering stage. The findings provides valuable guidance for N fertilizer application in alfalfa production on saline‒alkali soils.